Strategi Implementasi Digitalisasi Administrasi Pendidikan untuk Meningkatkan Efisiensi Operasional Sekolah - Zaeni Dahlan; Eda Laelasari; Winda Nidya Putri Fitriana (STAI Al-Hamidiyah Jakarta, 2026)
Digital transformation has now become an urgent necessity in the world of education, especially in administrative management. In the past, many school administrations were still entirely manual, resulting in slow processes, frequent data errors, and inefficiency. When information technology was introduced, everything changed; schools could adopt management information systems, e-administration, or digital data management that made all processes much faster and more organized. This article discusses strategies for implementing educational digitalization systems to make data management and school operations more efficient. The research method uses a literature study that analyzes scientific journals, books, and research reports regarding administrative digitalization. Based on that study, it explains that a well-designed digitalization strategy makes the work of educational staff lighter, processes data faster, increases transparency, and allows decisions to be made based on valid data while maintaining data security without disrupting school learning. Schools must be prepared in terms of technological infrastructure, possess a capable management information system, and ensure their educational staff is tech-savvy. Additionally, digitally literate leadership and data integration between systems are required so that everything runs in a connected manner. The success of this digitalization depends on how ready the school infrastructure is, how competent the human resources are, and how strong the policy support is from the institution. Digital transformation in educational administration needs to be carefully considered and executed in a planned manner to truly bring real change to the quality of educational services.